The Indispensable Role of Histone Methyltransferase PoDot1 in Extracellular Glycoside Hydrolase Biosynthesis of Penicillium oxalicum - Li, Yanan; Hu, Yueyan; Zhao, Kaili; Pan, Yunjun; Qu, Yinbo; Zhao, Jian; Qin, Yuqi (Frontiers in Microbiology, 2019)
Histone methylation is associated with transcription regulation, but its role for glycoside hydrolase (GH) biosynthesis is still poorly understood. We identified the histone H3 lysine 79 (H3K79) -specific methyltransferase PoDot1 in Penicillium oxalicum. PoDot1 affects conidiation by regulating the transcription of key regulators (BrlA, FlbC, and StuA) of asexual development and I s required in normal hyphae septum and branch formation by regulating the transcription of five septin-encoding genes, namely, aspA, aspB, aspC, aspD, and aspE. Tandem affinity purification/mass spectrometry showed that PoDot1 has no direct interaction with transcription machinery, but it affects the expressions of extracellular GH genes extensively. The expression of genes (amy15A, amy13A, cel7A/cbh1, cel61A, chi18A, cel3A/bgl1, xyn10A, cel7B/eg1, cel5B/eg2, and cel6A/cbh2) that encode the top 10 GHs were remarkably downregulated by Podot1 deletion (ΔPodot1). Consistent with the decrease in gene transcription level, the activities of amylases and cellulases were significantly decreased in ΔPodot1 mutants in agar (solid) and fermentation (liquid) media. The repression of GH gene expressions caused by PoDot1 deletion was not mediated by key transcription factors, such as AmyR, ClrB, CreA, and XlnR, but was accompanied by defects in global demethylated H3K79 (H3K79me2) and trimethylated H3K79 (H3K79me3). The impairment of H3K79me2 on specific GH gene loci was observed due to PoDot1 deletion. The results implies that defects of H3K79 methylation is the key reason of the downregulated transcription level of GH-encoding genes and reveals the indispensable role of PoDot1 in extracellular GH biosynthesis.